PROPERTIES OF ULTRAVIOLET EMISSION AT DEVELOPMENT OF SOLAR FLARES - G.S. Minasyants; T.M. Minasyants; V.D. Vdovichenko; A. G. Bibossinov (Academic Scientific Journal of Computer Science, 2019)
By means of processing photoheliograms in the λ1700Ǻ ultraviolet emission (temperature minimum, upper photosphere) obtained on the Solar Dynamics Observatory (SDO) spacecraft, the behavior of the relative intensity of bright plasma at the level of the photosphere during the development of impulsive phase of solar flares was studied. The interrelation of the course of change in flare ultraviolet emission with the profile of time derivative of the X-ray flux (1–8) Ǻ and with the value of enhancement in the density of electrons arising at development of flares has been revealed.